Mold Occurring on the Air Cleaner High-Efficiency Particulate Air Filters Used in the Houses of Child Patients with Atopic Dermatitis - Kim, Seong Hwan; Ahn, Geum Ran; Son, Seung Yeol; Bae, Gwi-Nam; Yun, Yeo Hong (KOREAN SOC MYCOLOGY, 2014)
Fungi are the known sources of irritation associated with atopic diseases (e.g., asthma, allergic rhinoconjunctivitis, and atopic eczema). To quantitatively estimate their presence in the indoor environment of atopic dermatitis-inflicted child patient's houses (ADCPHs), the high-efficiency particulate air (HEPA) filters installed inside the air cleaners of three different ADCPHs were investigated for the presence of mold. The air cleaner HEPA filters obtained from the three different ADCPHs were coded as HEPA-A, -B, and -C, respectively, and tested for the presence of mold. The colony forming units (CFUs) corresponding to the HEPA-A, -B, and -C filters were estimated to be 6.51 x 10(2) +/- 1.50 x 10(2) CFU/cm(2), 8.72 x 10(2) +/- 1.69 x 10(2) CFU/cm(2), and 9.71 x 10(2) +/- 1.35 x 10(2) CFU/cm(2), respectively. Aspergillus, Penicillium, Alternaria, Cladosporium, Trichoderma, and other fungal groups were detected in the 2,494 isolates. The distribution of these fungal groups differed among the three filters. Cladosporium was the major fungal group in filters HEPA-A and -C, whereas Penicillium was the major fungal group in the filter HEPA-B. Nine fungal species, including some of the known allergenic species, were identified in these isolates. Cladosporium cladosporioides was the most common mold among all the three filters. This is the first report on the presence of fungi in the air cleaner HEPA filters from ADCPHs in Korea.